PENGARUH PARTISIPASI ANGGOTA TERHADAP KEBERHASILAN KOPERASI - Khoiriyah, .; Asriati, Nuraini; ., Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This research is to know how influence member participation to success of cooperative. Variable in this research is independent variable (X) that is with aspect of member participation in decision making, capital contribution, utilization and member participation in cooperative supervision. The method used in this research is quantitative method. The population in this research is all employees of Cooperative Tirta Dharma Khatulistiwa PDAM Pontianak city. Data collection techniques are indirect communication techniques and documenter study techniques. While the data collection tool is questionnaire data (questionnaire).Data analysis technique in this research use statistic version 16.0. The results of the findings based on questionnaire data (questionnaire), to analyze the data of researchers using SPSS. This results in an effective contribution data analysis to the success of the Cooperative by 70%..Keyword: Member Participation, and Cooperative Success